2017
DOI: 10.1182/blood-2016-08-734210
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis is a feature of acute GVHD, and VEGFR-3 inhibition protects against experimental GVHD

Abstract: Lymph vessels play a crucial role in immune reactions in health and disease. In oncology the inhibition of lymphangiogenesis is an established therapeutic concept for reducing metastatic spreading of tumor cells. During allogeneic tissue transplantation, the inhibition of lymphangiogenesis has been successfully used to attenuate graft rejection. Despite its critical importance for tumor growth, alloimmune responses, and inflammation, the role of lymphangiogenesis has not been investigated during allogeneic hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…Indeed, R-Spo3 neutralization and to a much lesser extent R-Spo2 neutralization after intestinal injury impaired tissue regeneration, indicating the critical role of intrinsic R-Spo3 production in the homeostasis of gut tissues 10 . However, our results are in sharp contrast to a recent report showing that lymphatic vessels were increased in the intestine in GVHD and that inhibition of lymphangiogenesis ameliorated murine GVHD 28 . We enumerated LECs by flow cytometry, while the previous study used histological analysis in combination with immunohistochemistry of Lyve-1.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, R-Spo3 neutralization and to a much lesser extent R-Spo2 neutralization after intestinal injury impaired tissue regeneration, indicating the critical role of intrinsic R-Spo3 production in the homeostasis of gut tissues 10 . However, our results are in sharp contrast to a recent report showing that lymphatic vessels were increased in the intestine in GVHD and that inhibition of lymphangiogenesis ameliorated murine GVHD 28 . We enumerated LECs by flow cytometry, while the previous study used histological analysis in combination with immunohistochemistry of Lyve-1.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies have shown the therapeutic efficacy of blocking lymphangiogenesis to attenuate allogeneic immune responses. Prolonged allograft survival in experimental models of islet, tracheal, cardiac, and corneal transplantation has been reported [38] , [39] , [40] , [41] , [42] , [43] , and in addition, anti-FLT4 antibody ameliorated aGVHD and improved survival in murine models [44] . Our data demonstrated that VEGF-C expression was related to CR achievement after induction chemotherapy and changes in immune cell frequency according to VEGF-C mRNA expression in humans.…”
Section: Discussionmentioning
confidence: 99%
“…aGVHD models were used as described previously. [2][3][4] For chemotherapy based models, 7 days before bone marrow transplantation (BMT), female B6 or BDF mice received 20mg/kg/day busulfan (Sigma Aldrich, USA) i.p. on 5 consecutive days.…”
Section: Mice and Agvhd Experimentsmentioning
confidence: 99%
“…However, the 20%-25% of patients who fail initial treatment with steroids (steroid-refractory aGVHD [SR-aGVHD]) have very high mortality. 2,3 No standard treatment for SR-aGVHD is currently available, and its pathobiology is poorly understood, thereby hindering the development of novel therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%